New Transition Metal Oxo‐Thiostannate: Synthesis, Characterization, and Investigation of its Photocatalytic Properties. Issue 4 (23rd January 2019) - Benkada, Assma; Poschmann, Michael; Näther, Christian; Bensch, Wolfgang
Abstract : The new transition metal oxo‐thiostannate [Ni(cyclen)]6 [Sn6 S12 O2 (OH)6 ]· 2(ClO4 )· 19H2 O (1 ) was prepared under hydrothermal conditions using Na4 SnS4 · 14H2 O and [Ni(cyclen)](ClO4 )2 as reactants. In the crystal structure the rare [Sn6 S12 O2 (OH)6 ] 10– anion is observed, which is composed of SnS2 O(OH)3 and SnS4 O2 octahedra, and SnS4 tetrahedra sharing edges and corners. The anion is expanded by six Ni 2+ centered complexes via Ni–S and Ni–OH bonds. The photocatalytic properties for the visible light driven hydrogen evolution reaction shows that 26.6 mmol· g –1 H2 were evolved after 3 h. Abstract :